PENGATURAN HUKUM TERHADAP KETERLIBATAN ANAK SEBAGAI PENGEDAR NARKOTIKA MENURUT UNDANG-UNDANG DI INDONESIA - Andini Pratiwi Siregar (Ilmu Hukum Prima (IHP), 2020)
The legal arrangement of the involvement of children as narcoticsdealer according to the law in Indonesia is regulated in theprovisions of Law Number 35 Year 2009 on Narcotics as thebackground of the law threatened to the child for his act ofdistributing narcotics. Then Law no. 11 Year 2012 on the CriminalJustice System of the Child as the basis for the criminalization of thechild if the child commits a narcotic crime and Law Number 23 Year2002 As Changed By Law of the Republic of Indonesia Number 35Year 2014 as the basis for the implementation of child protectionthat has been proven to circulate narcotics.